A set of sampling, preparation, and staining techniques for studying meiosis in cucumber. (June 2022) - Li, Junhua; Guo, Jinjin; Wei, Chenchen; Meng, Yao; Wang, Xiaoduan; Yu, Panpan; Yang, Lin; Liang, Yi; Guo, Siyi; Yuan, Jinhong
Abstract: The development of genetic and genomic resources for biological studies in cucumber has experienced an unprecedented boom in recent years. To investigate the function of putative meiotic genes and germplasm in breeding programs, an accurate cytogenetic characterization is required. Cytological methods and reference to investigate meiosis in cucumber are limited at present. Here we provide a set of cytological techniques that have been adapted for the study of meiosis in cucumber. The meiotic stages can be identified with high precision using hierarchical criteria from developing buds, undisturbed meiocytes, and freshly stained chromosomes. A meiotic cytological atlas of all stages is presented as a reference for identifying particular stages and for comparison of meiosis between normal and mutant plants. We performed a comparative analysis of the distribution of cytoplasmic organelles between cucumber and Arabidopsis, and we described a highly nonsynchronous condensation of chromosome parts during diplotene. A simplified fluorescence in situ hybridization (FISH) protocol, using robustly spread chromosomes, were developed. In addition, we designed a single oligonucleotide probe for 5S rDNA to use in karyotyping and monitoring of homologous chromosome pairing, which will make FISH analysis of 5S rDNA easier and more economical. Highlights: Techniques for meiosis staging, chromosome preparation and FISH in cucumber. A cytological atlas of cucumber meiosis is provided for reference. A non-synchronous chromosome parts during diplotene is described. We designed a single oligonucleotide probe for 5S rDNA to monitor homologous pairing.